(untitled) (Commonwealth Journal of Local Governance, 2024)
This paper presents the author’s reflections on efforts to advance the scope and role of elected local government in the Pacific Islands. It focuses primarily on the Commonwealth Local Government Forum Pacific Project, which has been operating since 2000, but also looks at broader issues around decentralisation and devolution, legislation and funding for local government, democracy and good governance, promoting better practice, sustainability and resilience, and the importance of a sound evidence base for developmental programmes and projects.